ANALISIS EFEKTIVITAS MODEL PEMBIAYAAN SYARIAH DALAM PENGEMBANGAN UMKM: STUDI PADA FINTECH ALAMI SHARIA - Sabrina Azzahra, (2023)
The development of the number of MSMEs in Indonesia which continues to increase, is accompanied by the development of fintech in Indonesia which continues to increase, triggered by the rapid advances in information and communication technology, there is a large market demand for easy access to financial services. But there are some problems faced, namely the problem of financing. The emergence of fintech in Indonesia makes it easier for people to obtain venture capital, financing business capital through fintech applications, where the flow of applying for financing is easier than financing to banks. This research method uses descriptive qualitative methods through case studies. In this study, the authors aimed to analyze the effectiveness of the Islamic financing model used in Islamic fintech, and its impact on the development of MSMEs. The results of this study indicate that the sharia financing mechanism in ALAMI SHARIAH is easy and can be done online, making it very easy for MSME actors to obtain business capital. By having business capital, MSME actors can run their business smoothly due to stable cash flow. It can be concluded that Islamic financing in the ALAMI SHARIA fintech is effective in developing MSMEs.